TEKNIK PENGOLAHAN IKAN LAUT - P, Sutriyati; Badraningsih, Badraningsih; E, Prihastuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The training  of the  fish  processing   is meant  to socialize  knowledge and skills  in fish processing   safety  and healthy  to be consumed  for the  fish sellers in Trisik  Beach,  Kulon  Progo,  Yogyakarta.The  15 fish  sellers  attended   the  training  from  Trisik  Village.   The training  was  conducted   5 times  consisting  of  one  session  of  theory  and  4 sessions   of   a  practices.    The   methods    of   the   training   were   lecturing, demonstrating   and practicing   on the spot. The evaluation  was done  after the training had finished.The result  of the  training  showed  that  the participants   mastered   thetraining   material   given   covering:    1)  hygiene   in  fish  processing,    2)  fish processing   for  preserving   products   i.e  fish  crackered   and  smoked,   and  3) fish processing  for ready-served   food  such as siomay,  ikan acar kuning and saos asam manis that  are served  hygienically.  The result of the training  has been applied  in warung  PKK Trisik  Village,  Kulon Progo, Yogyakarta.Key word: training.fish  processing